2014
DOI: 10.1002/clen.201300882
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity, Ecotype Hybrid, and Mixture of Invasive Spartina alterniflora Loisel in Coastal China

Abstract: Spartina alterniflora, a native species at the east coast of North America, is currently the focus of increasing management concern due to its rapid expansion in coastal China. To better understand the plant traits associated with the success of invasion, we examined the genetic variation and the possible existence and distribution of ecotype hybrids and ecotype mixtures of the species in China. We collected and analyzed 144 samples from seven populations throughout coastal China (21.6°–38.6°N; 109.7°–121.8°E)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 51 publications
(94 reference statements)
3
23
1
Order By: Relevance
“…This prediction is underscored by the observation of reduced morphological diversity in S. alterniflora in South America. Xia et al (2014) found that, as expected, introduced S. alterniflora in China (originally from North Carolina, Georgia and Florida) have low genetic diversity compared to North American Atlantic populations. They noted that ecotype hybrids and ecotype mixtures in China may be contributing to the species' robust success there.…”
Section: Discussionsupporting
confidence: 73%
“…This prediction is underscored by the observation of reduced morphological diversity in S. alterniflora in South America. Xia et al (2014) found that, as expected, introduced S. alterniflora in China (originally from North Carolina, Georgia and Florida) have low genetic diversity compared to North American Atlantic populations. They noted that ecotype hybrids and ecotype mixtures in China may be contributing to the species' robust success there.…”
Section: Discussionsupporting
confidence: 73%
“…Bigger pies in (a) and (b) shows the relative frequencies of the haplotypes. The haplotypes from additional three sites in the Gulf of Mexico were from the literature as cited TA B L E 1 The sampling locations, time of introductions (Li et al, 2009;Wang et al, 2015;Xia, Zhao, Yang, & An, 2015;Xu & Zhuo, 1985;Zhang et al, 2017) Note: The sample sizes are the number of sampled clones per population for the (north/mid-/south) gardens and alternative experiments. The regions within the invasive range are differentiated according to the differentiation among geographic, climatic and tide range variables ( Figure 1 and Figure S2), and the regions within the native range are defined following Blum et al (2007) and Bernik et al (2016).…”
Section: The Population Genetic Surveymentioning
confidence: 99%
“…In 1979, hundreds of plants and half a kilogram of seeds of S. alterniflora were introduced in China for ecological engineering from populations in Morehead City in North Carolina, Sapelo Island in Georgia, and Tampa Bay in Florida by Zhong and his colleagues of Nanjing University (Xu and Zhuo, 1985). Because of different introductions over a large geographic area, S. alterniflora rapidly spread across the coastal marshes of China, with its current range now extending from Liaoning in north to Guangxi in the south (Xia et al, 2015;Qiao et al, 2019). In fact, there have been multiple introductions of S. alterniflora into Willapa Bay, USA, and new genotypes have been generated by admixture following secondary contact among previously allopatric native populations (Civille et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there have been multiple introductions of S. alterniflora into Willapa Bay, USA, and new genotypes have been generated by admixture following secondary contact among previously allopatric native populations (Civille et al, 2005). Because the origins of China's S. alterniflora are three allopatric native populations in the United States, An et al (2007) and Xia et al (2015) considered that admixture and hybridization of S. alterniflora of different origins might increase genetic variation within the invasive population, and hybrids have stronger environmental tolerance and thus have higher growth rates than native congeners. Because of heterosis, the offspring produced by intraspecific hybridization often show stronger adaptability than their parents; therefore, multiple introductions were considered an important factor to promote successful invasion (Geller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation